Generating Mobile Virtual Tour Using UAV and 360 Degree Panorama for Geography-Environmental Learning in Higher Educationw - Masruroh, Heni; Sahrina, Alfi; Al Khalidy, Diky; Trihatmoko, Edy (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Nowadays, the limitations of media in geo-environmental learning present a significant challenge, as media plays an indispensable role in fostering students’ comprehensive understanding. Employing technology capable of delivering comprehensive landscape information is crucial for effective environmental education. Utilizing Unmanned Aerial Vehicles (UAVs) and 360-degree panoramic cameras represents a judicious technological choice, which can be seamlessly integrated into virtual tours. This research aims to develop a Mobile Virtual Tour (Movie-Tour) as a medium to support learning, especially for materials regarding environmental geography. The research and development (RnD) method is used in research with the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). Data collection for the development of the product involved conducting a need assessment, performing validation tests and conducting trials with students. To gather field data for creating environmental geography materials for the Movie-Tour product, we utilized an Unmanned Aerial Vehicle (UAV) and a 360-degree stereoscopic camera. The results demonstrate that Movie- Tour is an educational medium capable of delivering an immersive learning experience and comprehensive materials, allowing for the virtual visualization of real-world conditions in the field. This capability enhances students’ engagement in exploring physical geography conditions, fosters independent knowledge acquisition, and nurtures their innate curiosity. Movie-Tour stands as a potent and practical educational tool, offering an effective and secure learning experience for students, eliminating the need for direct field visits.